Perbedaan Perkembangan Motorik Kasar, Bahasa dan Perilaku Prososial pada Anak dengan Pembelajaran Program Fullday dan Reguler - Ernita Ernita; Marlina Marlina; Serlis Mawarni (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze differences in gross motor development, language, and prosocial behavior in children undergoing full-day and regular Kindergarten learning at Bunnaya Kindergarten Lhokseumawe, Lhokseumawe City. This study used a quantitative and comparative descriptive method, with the KPSP instrument for ages 4-6 years. The results showed that there were significant differences in gross motor development (p-value = 0.000, (p-value = 0.000) and prosocial behavior (p-value = 0.001) in total day and regular program children. In conclusion, the two groups can cause differences in significant child development. The gross motoric product of children aged 4-6 years in Lhokseumawe is dominant under normal conditions, where the regular program has a more significant percentage of normal than whole day school. The development of language skills is chief under normal conditions, where the school program, either full-day or regular program, has the same percentage. In social behavior, children in Lhokseumawe have high social behavior, namely 62.5%. The social behavior of children with the full-day program is slightly higher than children with the regular schedule. Keywords: Language, Fullday, Gross Motor, Prosocial Behavior, Regular